D-dimer Strategy in Thrombosis Exclusion - Freyburger, G.; Trillaud, H.; Labrouche, S.; Gauthier, P.; Javorschi, S.; Bernard, P.; Grenier, N. (Thrombosis and Haemostasis, 1998)
DD are now recognized as a valuable tool to screen patients suspected of deep venous thrombosis or pulmonary embolism before carrying out a gold standard radiologic examination. The newest methods available claim to be able to ascertain the absence of thrombosis, but they have yet to prove their efficiency. We compared the performances of 3 reference ELISA methods (D-DI Asserachrom™ Stago, D-dimer Enzygnost™ Behring and Dimertest GOLD EIA™ Agen), 5 recent rapid methods (VIDAS D-Dimer™ bioMérieux, Instant IA™ Stago, Simplired™ Agen, Nycocard D-dimer™ Nycomed and Accuclot D-Dimer™ Sigma Diagnostics) and two routine latex methods (Dimertest™ American Diagnostica and FDP-Slidex™ bioMérieux) in 100 patients. One of the rapid quantitative methods was demonstrated to have a level of efficiency comparable to that of ELISA methods. Finally, the cost and efficiency of different strategies were evaluated, the association of a routine latex method with the VIDAS D-Dimer™ bioMérieux being proven to be the most efficient.